2022
DOI: 10.1016/j.athoracsur.2021.07.097
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Management, and Outcomes of Patients With COVID-19 and Pneumothorax

Abstract: BACKGROUND Our objective was to report the incidence, management, and outcomes of patients who developed a secondary pneumothorax while admitted for coronavirus disease 2019 (COVID-19).METHODS A single-institution, retrospective review of patients admitted for COVID-19 with a diagnosis of pneumothorax between March 1, 2020, and April 30, 2020, was performed. The primary assessment was the incidence of pneumothorax. Secondarily, we analyzed clinical outcomes of patients requiring tube thoracostomy, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 12 publications
1
20
1
Order By: Relevance
“…Previous retrospective and observational studies have shown that the incidence of pneumothorax is 1% in patients with COVID-19 pneumonia who need hospitalization, 2% in those who need intensive care treatment, and 5.9–15% in those receiving IMV ( 3 5 ). In a recent retrospective review examining 1,595 patients with COVID-19, pneumothorax occurred in 7% of patients, among whom IMV-related pneumothorax was diagnosed in 80% ( 1 ). Another retrospective study that examined 601 patients with COVID-19 pneumonia requiring IMV also supported the above epidemiological findings ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous retrospective and observational studies have shown that the incidence of pneumothorax is 1% in patients with COVID-19 pneumonia who need hospitalization, 2% in those who need intensive care treatment, and 5.9–15% in those receiving IMV ( 3 5 ). In a recent retrospective review examining 1,595 patients with COVID-19, pneumothorax occurred in 7% of patients, among whom IMV-related pneumothorax was diagnosed in 80% ( 1 ). Another retrospective study that examined 601 patients with COVID-19 pneumonia requiring IMV also supported the above epidemiological findings ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, pneumothorax occurs spontaneously in patients with COVID-19 pneumonia even in the absence of pre-existing lung disease or the need for IMV ( 6 ). Approximately 20% of patients with COVID-19 develop ARDS, which requires IMV ( 1 ). Given the high incidence rate of pneumothorax complicated by COVID-19-related ARDS, early detection and management of COVID-19-related pneumothorax is essential.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations